Efektivitas Program Lonto Leok Berbasis Rumah Gendang dalam Pencegahan dan Penanganan Stunting di Manggarai - Parus, Agnesia Nimat; Andur, Elisabet Sunariati; Esi, Maria Goreti; Nanur, Fransiska Nova (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
Stunting has still become a serious problem in Indonesia, including Manggarai Regency in the East Nusa Tenggara Province, where the prevalence of stunting increased to 23.5% in 2020. This study aims to evaluate the effectiveness of the Lonto Leok program based on Rumah Gendang in the prevention and treatment of stunting and analysis of the inhibiting factors. The research was conducted in Ling Village, North Satarmese District, Manggarai Regency, East Nusa Tenggara using qualitative methods with a descriptive design. The research population was all parties involved in the program, and the sample was taken purposively. The instrument used is in-depth interviews conducted with the eight key participants including the head of the public health sector at the Manggarai District Health Office, village midwives, community leaders, pregnant women, and parents of stunting toddlers. The data was analyzed thematically. The results showed that the Lonto Leok program based on the Gendang House had not been effective in preventing and dealing with stunting problems because of the lack of community commitment to implement the agreements that had been discussed during implementation. Regular monitoring and evaluation are needed from related parties so that this program is really useful in preventing and dealing with stunting problems.